2016
DOI: 10.1002/mabi.201500388
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Copolymers Shuttle Drugs Across the Blood–Brain Barrier

Abstract: Medical treatment of diseases of the central nervous system requires transport of drugs across the blood-brain barrier (BBB). Here, it is extended previously in vitro experiments with a model compound to show that the non-water-soluble and brain-impermeable drug domperidone (DOM) itself can be enriched in the brain by use of an amphiphilic copolymer as a carrier. This carrier consists of poly(N-(2-hydroxypropyl)-methacrylamide), statistically copolymerized with 10 mol% hydrophobic lauryl methacrylate, into who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…[45][46][47][48] In addition, Zentel and co-workers could show that also am-phiphilic copolymers based on 2-hydropropylacrylamide and laurylacrylate could increase transport of small molecules across the BBB in vitro and in vivo. [49][50][51]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47][48] In addition, Zentel and co-workers could show that also am-phiphilic copolymers based on 2-hydropropylacrylamide and laurylacrylate could increase transport of small molecules across the BBB in vitro and in vivo. [49][50][51]…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that bothcoated and uncoated nanoparticleswere able to penetrate the BBB in vivo , reaching the maximum brain concentration 1 h postintravenous injection. Pioneering work by Kabanov and co-workers revealed that several amphiphilic polymers can facilitate the transport of small molecules and proteins across the BBB. In addition, Zentel and co-workers could show that also amphiphilic copolymers based on 2-hydropropylacrylamide and laurylacrylate could increase the transport of small molecules across the BBB in vitro and in vivo . …”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitation of the blood–brain barrier (BBB), medicine cannot be effectively sent to the expected diseased region . As previously reported, the efficiency of drug delivery to the brain has been shown to be reduced to less than 5% . This intractable disease requires a traceable and effective delivery system.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, our findings on the different blood components suggested that the homopolymer interacts with serum proteins and with blood cells. Former studies of our group showed that HPMA- ran -LMA copolymers interact with very low density lipoproteins in the blood [ 42 ] and with cell membranes [ 43 , 44 ]. Not only structure and size of the polymer but furthermore the cell type is crucial for polymer delivery.…”
Section: Discussionmentioning
confidence: 99%